PENGARUH PEMBERIAN COOKIES MOLEBA (TEPUNG MOCAF, TEPUNG IKAN LELE, DAN BAYAM MERAH ) UNTUK MENINGKATKAN KADAR HAEMOGLOBIN REMAJA PUTRI DI SMK UTAMA BAKTI PALEMBANG - Yudanti, Kartika; Telisa, Imelda; Terati, Terati (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Adolescent anemia is a nutritional problem caused by iron deficiency in the blood, especially in adolescent girls. Moleba Cookies (mocaf flour, catfish, and spinach) are one of alternative snack for anemia sufferers. In 100 gr of Moleba Cookies contains 12.6% protein and 4.36 mg of iron which can meet the iron requirement of 29% per day. The purpose of this study was to determine whether Moleba cookies increase hemoglobin levels in adolescent girls suffering from anemia at SMK Utama Bakti Palembang. The research design used was a quasi-experiment, with a pre-test and post-test design with one group, and the research time was 7 days, with the provision of 100 gr of cookies for 2 snacks a day. The research sample consisted of 33 adolescent girls suffering from anemia at SMK Utama Bakti Palembang. The sample was selected using accidental sampling. Initial and final Hb level examinations were carried out by laboratory health workers using the Easy Touch GCHB tool. The results of data analysis using independent t-test showed an average difference in the increase in Hemoglobin levels before and after the intervention of 1.31 g/dL. The average Hemoglobin level before the intervention was 10.91 g/dL with a p-value <0.05 (0.000), the average Hemoglobin level after the intervention was 12.22 g/dL with a p-value <0.05 (0.000). The results of the statistical test (independent t-test) showed that there was an effect of giving Moleba cookies to increase Hemoglobin levels in female adolescents with Anemia at SMK Utama Bakti Palembang (p-value = 0.000).